The Collection of Zoosporic Eufungi at the University of Michigan (CZEUM): introducing a new repository of barcoded Chytridiomyceta and Blastocladiomycota cultures - D. Rabern Simmons; Anne E. Bonds; Buck T. Castillo; Rebecca A. Clemons; Alex D. Glasco; Jillian M. Myers; Natasha Thapa; Peter M. Letcher; Martha J. Powell; Joyce E. Longcore; Timothy Y. James (IMA Fungus)
Abstract We formed the Collection of Zoosporic Eufungi at the University of Michigan (CZEUM) in 2018 as a cryopreserved fungal collection consolidating the University of Maine Culture Collection (UMCC, or JEL), the University of Alabama Chytrid Culture Collection (UACCC), and additional zoosporic eufungal accessions. The CZEUM is established as a community resource containing 1045 cryopreserved cultures of Chytridiomycota, Monoblepharidomycota, and Blastocladiomycota, with 52 cultures being ex-type strains. We molecularly characterized 431 cultures by amplifying the majority of the rDNA operon in a single reaction, yielding an average fragment length of 4739 bp. We sequenced multiplexed samples with an Oxford Nanopore Technology MinION device and software, and demonstrate the method is accurate by producing sequences identical to published Sanger sequences. With these data, we generated a phylogeny of 882 zoosporic eufungi strains to produce the most comprehensive phylogeny of these taxa to date. The CZEUM is thus largely characterized by molecular data, which can guide instructors and researchers on future studies of these organisms. Cultures from the CZEUM can be purchased through an online portal.